Lingkungan Internal Bersahabat Pewirausahawan Masehi Advent Hari Ketujuh Kabupaten Minahasa Utara - Rantung, Danny Ivan (JBE (Journal of Business and Economics); Volume 7 No.1, 2008 JBE UNKLAB, 2008)
The present conditions in Indonesia society makes this listing of role demands and required characteristics of entrepreneurs essential to ensure that people know what they are going into before embarking on entrepreneurship.  This way, resources are put into ventures with some chance of success rather than just a gamble also it may be worthwhile to note that the Indonesia entrepreneur today must not just operate with the give in Indonesia environment, rather than just be reactive.  He needs to be intensely involved in the process of changing the country for the better.  He should be entrepreneur both for his firm and for the nation.This research study analyses entrepreneurial characteristics and managerial skills of business men in selected small scale enterprises in Minahasa Utara.  This study aims to answer the profile of respondents to what extent do the respondents perceive their entrepreneurial characteristics and how do they vary in terms of the perceived entrepreneurial characteristics of the respondents,  to what extent are the following managerial skills being utilized by the respondents, and how do they vary  in terms of the extent to which managerial skills are being utilized by the respondents. The method used in this research was the descriptive method survey.  The main instrument used to gather the data was the questionnaire.  Unstructured interview with the small businessmen.  Owners or managers were also conducted to obtain supplementary data.  In order to establish the validity of the questionnaire, a dry run was likewise conducted.  The sample respondents of the study were owners or managers of small scale industries in Minahasa. The hypothesis were tested with the use of the T-test for significant differences involving two factors test or Analysis of Variance (ANOVA) for significant differences involving 3 or more factors.  The perceived entrepreneurial characteristics do not differ significantly among the respondents when group according to: age, sex, educational attainment, net income level, business activities.   The extent to which managerial skills are utilized do not differ significantly among the respondents when grouped according to  age, sex, educational attainment, net income level and business activities.